Lumbar Spine: Reliability of MR Imaging Findings - Carrino, John A.; Lurie, Jon D.; Tosteson, Anna N. A.; Tosteson, Tor D.; Carragee, Eugene J.; Kaiser, Jay; Grove, Margaret R.; Blood, Emily; Pearson, Loretta H.; Weinstein, James N.; Herzog, Richard (Radiology, 2009)
To characterize the inter- and intraobserver variability of qualitative, non-disk contour degenerative findings of the lumbar spine at magnetic resonance (MR) imaging. The case accrual method used to perform this institutional review board-approved, HIPAA-compliant retrospective study was the random selection of 111 interpretable MR examination cases of subjects from the Spine Patient Outcomes Research Trial. The subjects were aged 18-87 years (mean, 53 years +/- 16 [standard deviation]). Four independent readers rated the cases according to defined criteria. A subsample of 40 MR examination cases was selected for reevaluation at least 1 month later. The following findings were assessed: spondylolisthesis, disk degeneration, marrow endplate abnormality (Modic changes), posterior anular hyperintense zone (HIZ), and facet arthropathy. Inter- and intraobserver agreement in rating the data was summarized by using weighted kappa statistics. Interobserver agreement was good (kappa = 0.66) in rating disk degeneration and moderate in rating spondylolisthesis (kappa = 0.55), Modic changes (kappa = 0.59), facet arthropathy (kappa = 0.54), and posterior HIZ (kappa = 0.44). Interobserver agreement in rating the extent of Modic changes was moderate: kappa Values were 0.43 for determining superior anteroposterior extent, 0.47 for determining superior craniocaudal extent, 0.57 for determining inferior anteroposterior extent, and 0.48 for determining inferior craniocaudal extent. Intraobserver agreement was good in rating spondylolisthesis (kappa = 0.66), disk degeneration (kappa = 0.74), Modic changes (kappa = 0.64), facet arthropathy (kappa = 0.69), and posterior HIZ (kappa = 0.67). Intraobserver agreement in rating the extent of Modic changes was moderate, with kappa values of 0.54 for superior anteroposterior, 0.60 for inferior anteroposterior, 0.50 for superior craniocaudal, and 0.60 for inferior craniocaudal extent determinations. The interpretation of general lumbar spine MR characteristics has sufficient reliability to warrant the further evaluation of these features as potential prognostic indicators.